2015
DOI: 10.4172/2161-0940.s4-004
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Characteristics of Rat Testicular Tissue and the Impact of Chronic Noise Stress Exposure in the Prenatal and Postnatal Periods

Abstract: Recently claims have been raised that noise stress may exert adverse effects on the reproductive functions. The present study was undertaken to investigate first; developmental histological characteristics of rat testis at 3 critical age periods namely; full term fetus, pre-pubertal and adult stages. Second, the impact of chronic noise stress exposure on testicular tissue at these age periods.Albino rats were used and assigned into 3 groups; pregnant rats (to obtain fetuses at day 20 of gestation), prepubertal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…On the contrary, the morphological presence of canalized lumen in the seminiferous tubules of pubertal to aged cane rats could be linked to the possible spermiogenetic activities occurring in their seminiferous epithelium. The testicular histology observed in the prepubertal rats in this study is similar to those reported for immature rats[ 34 ] and some young avian species. [ 23 ]…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…On the contrary, the morphological presence of canalized lumen in the seminiferous tubules of pubertal to aged cane rats could be linked to the possible spermiogenetic activities occurring in their seminiferous epithelium. The testicular histology observed in the prepubertal rats in this study is similar to those reported for immature rats[ 34 ] and some young avian species. [ 23 ]…”
Section: Discussionsupporting
confidence: 87%
“…The observed age-related changes in the testicular morphophysiology of cane rats were similar to previously reported works. [ 34 35 36 37 ]…”
Section: Discussionmentioning
confidence: 99%
“…Noise is one of the occupational stressors that have not been well studied. People, especially young people and pregnant women should be aware of the dangers of exposure to high levels of noise, particularly the impact on reproduction (13).…”
Section: Discussionmentioning
confidence: 99%
“…LH and FSH and major changes in sperm parameters among workers exposed to noises as loud as 119 dB(6). Lasheen et al showed that noise stress led to histopathological changes in testes; it increased the number of apoptosis and reduced the number and size of seminiferous tubules in prenatal and postpartum groups(13). days(40).…”
mentioning
confidence: 99%